Goniasteridae - Mah, Christopher L. (Zenodo, 2020)
GONIASTERIDAE The Goniasteridae is the most taxon-rich group within the Asteroidea, including over 270 species in approximately 70 genera with many new species being described (e.g., Mah 2019). Although an overview of the group is presented in Clark and Downey (1992), Halpern (1970) provided an extensive treatment on Goniasteridae from the tropical Atlantic. Although several subfamilies have been recognized, the most frequently encountered group on the Okeanos Explorer surveys is the Hippasterinae, which includes multiple genera that are now all known to feed on deep-sea octocorals and scleractinians (e.g. Mah 2015b, Mah et al . 2010). All of the genera within the Hippasterinae, Hippasteria , Evoplosoma , Gilbertaster and Sthenaster were observed during the surveys included herein. Corallivory has been reported among many Pacific goniasterid taxa (Mah 2006, Mah 2015a) whose biology and feeding habits had been previously unknown suggesting that the group, as a whole, is likely significant to understanding the ecology of deep-sea coral habitats. Undescribed Goniasteridae sp. 1 Figure 6A This species was characterized by its strongly stellate body shape (R/r=~4.0) with elongate, tapering arms and weakly curved to straight interradial arcs. Abactinal plates were abutted and were part of a relatively even surface with no spines or other primary accessories (i.e. tubercles, etc.). Fine, widely spaced granules were observed on the surface of the abactinal and superomarginal plates. Arm plates appeared similar in size to those on disk. Superomarginal plates appeared strongly convex, wide and were dark in color relative to disk and peripheral coloration. Distalmost inferomarginal plates possessed sharp tubercles or small spines. Color in life was white with brown highlights on disk and central surface of marginal plates. This species could not be fully reconciled with known taxa, suggesting a likely new genus and species. No specimen was collected. This species’ abactinal plate and arm shape suggests comparison Circeaster americanus , but abactinal arm plates appeared relatively similar in size and arms were much more elongate than known specimens. The superomarginal plates and apparently convex superomarginal plates are also different from Circeaster. The elongate arms and marginal plates also suggest similarity with Evoplosoma , although the extensive spination on the abactinal or marginal plates and the pulpy body surface was not present. Feeding Observations The three images of this species all showed it on hard, rocky vertical substratum. Two of the images show one of the arms extended off the substrate into the area above the animal. One of the Florida Escarpment observations (at 2006 m) shows a stalk of possibly coral, bryozoan or some other flocculent material emerging from below the oral surface. Possible food was not observed on the other image with the extended arm but the behavior might have been indicative of possible feeding. Occurrence: Incised Escarpment Ridge and Northwest Florida Escarpment, Gulf of Mexico, 2060–2178 m. Images Examined Incised Escarpment Ridge, Gulf of Mexico, 27.35241, -85.43421, 2060 m EX1711_IMG_20171204T172534Z_ROVHD.jpg NW Florida Escarpment, Gulf of Mexico, 28.12419, -86.6575, 2178 m EX1803_IMG_20180426T163320Z_ROVHD.jpg NW Florida Escarpment, Gulf of Mexico, 28.12527, -86.65618, 2006 m EX1803_IMG_20180426T181615Z_ROVHD.jpg : Published as part of Mah, Christopher L., 2020, New species, occurrence records and observations of predation by deep-sea Asteroidea (Echinodermata) from the North Atlantic by NOAA ship Okeanos Explorer, pp. 201-260 in Zootaxa 4766 (2) on pages 215-216, DOI: 10.11646/zootaxa.4766.2.1, http://zenodo.org/record/3764018 : {"references": ["Clark, A. M. & Downey, M. E. (1992) Starfishes of the Atlantic. Chapman and Hall, London, 794 pp.", "Halpern, J. A. (1970) Biological investigations of the deep sea. 51. Goniasteridae (Echinodermata: Asteroidea) of the Straits of Florida. Bulletin of Marine Science, 20 (1), 193 - 286.", "Mah, C. L. (2015 b) A new Atlantic species of Evoplosoma with taxonomic summary and in situ observations of Atlantic deep-sea corallivorous Goniasteridae (Valvatida; Asteroidea). Marine Biodiversity Records, 8 (e 5), 1 - 8. https: // doi. org / 10.1017 / S 1755267214001407", "Mah, C. L., Nizinski, M. & Lundsten, L. (2010) Phylogenetic Revision of the Hippasterinae (Goniasteridae; Asteroidea): Systematics of Deep Sea Corallivores, including one new genus and three new species. Zoological Journal of the Linnean Society, 160, 266 - 301, 11 figs. https: // doi. org / 10.1111 / j. 1096 - 3642.2010.00638. x", "Mah, C. L. (2006) Phylogeny and biogeography of the deep-sea goniasterid, Circeaster (Echinodermata: Asteroidea) including descriptions of six new species. Zoosystema, 28 (4), 917 - 954.", "Mah, C. L. (2015 a) New species, corallivory, in situ video observations and overview of the Goniasteridae (Valvatida, Asteroidea) in the Hawaiian Region. Zootaxa, 3926 (2), 211 - 228. https: // doi. org / 10.11646 / zootaxa. 3926.2.3"]}